Death Penalty in the National Criminal Code Versus Human Rights - Malau, Parningotan (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Pancasila is the basis of the state in Indonesia. Countries have several types of legal rules enforced according to the crime rate of the offender. Mistakes in responding to state law lead to wrong actions. The purpose of this study is to increase legal awareness of the people in Indonesia through preventive action, namely that criminals are expected not to commit crimes because they have received a deterrent effect from punishment. Research method with normative juridical. Data analysis techniques through analysis of electronic journals, e-books and reference searches through Google Scholar. The results of the study show that the types of punishment in Indonesia have different levels according to the treatment of the crime. The heaviest consequence in serving the Death Penalty. On the basis of errors in acts of corruption and other cases. The death penalty can apply to life imprisonment, shot to death based on the judge's decision.